The Behavior of High Scanning Electron Voltage in SEM Due to Mirror Effect - Tareq Hashim Abbood (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
To determine the factors influencing the electron scattering process in a scanning electron microscope caused by the electron mirror, a set of physical and mathematical ideas were used. These equations, which relate the scattering of the input electron with the surface potential energy of the dielectric material under examination using a matched beam ion microscope and scanning electrons, are based on simplified engineering mathematics. After five minutes of charging the insulator to saturation with an acceleration voltage of 30 kV, the accumulated charge was 0.3 nC, from which the surface voltage across the working distance (WD = 15 mm) was determined. The scattering angle (β) was found to be inversely proportional to the incidence angle (θ) in the second stage, when scanning voltages (Vsc=2, 4, and 6 kV) were employed. This was because the angle between the incident and scattered electron (2
Keywords: Electron Trajectory; Electron Mirror Effect; Scanning Electron Microscope